A new species and a new record of Horaeomorphus Schaufuss (Staphylinidae: Scydmaeninae: Glandulariini) from China - Zhou, De-Yao; Yin, Zi-Wei (Zootaxa, 2018)
A new species of the genus Horaeomorphus Schaufuss, H. xiweii Zhou & Yin, sp. n., is described from Yunnan, southwestern China, and a new country record for H. solodovnikovi Jałoszyński is given (i.e., China). Diagnostic features of both species are illustrated.